The Teachings of Jihad in The Involvement of Samaniyah Tarekate in The War of Menteng 1819: A Historical Analysis - Arditya Prayogi; M. Rifa’i Subhi; Rhischa Assabet Shilla (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
Sufism is often accused of causing the decline of Islam because its teachings are full of fatalism, occultism, escapism, and irrationalism. Adherents of the trek are also often regarded as an exclusive, selfish, and asocial community. But in fact, the existence of Sufism can go hand in hand with the teachings of jihad, which is one of the teachings with values that are contrary to the assumption of the importance of Sufism. This article aims to reveal that the trek's practice in its history moved the spirit of struggle. This article was written using historical methods such as heuristics, criticism, interpretation, and historiography. It can be concluded in this article that the teachings of jihad can be well applied to tarekat adherents, especially to the Samaniyah order in the Menteng war incident. The involvement of the Samaniyah orders in the Menteng war proved that Sufism, apart from being identical to the spiritual dimension, could also move into the social size. The teachings of jihad introduced by Abd Shomad al-Palimbani, as well as his students' involvement, became the key to the participation of the Samaniyah order in the Menteng war of 1819, which led to the victory of the Palembang side over the Dutch in the Menteng war of 1819.